Sudan virus disease outbreak in Uganda: urgent research gaps - Duduzile Edith Ndwandwe; Alice Norton; Susan Khader Ibrahim; Katherina Thomas (BMJ Global Health, 2022)
The Sudan ebolavirus (SUDV) outbreak highlights our ongoing vulnerability to re-emerging high-consequence infectious diseases. Although the Minister of health in Uganda has initiated public health measures in collaboration with neighbouring countries and with support of the WHO, cases have continued to spread to several regions including the capital. The ongoing transmission, uncertain case numbers and no licensed vaccine or therapeutics available are a cause for concern. We searched four databases for SUDV research using the search terms “SUDV”, “Sudan Virus” and “Ebola Sudan”. Our analysis identified only 20 SUDV research studies. Most were implemented in the USA and only one in Uganda. Nine studies were on therapeutics, eight on vaccines, one on diagnostics, one in one health and one in social science. Our data highlight a lack of SUDV research and an urgent need for investment to identify an effective vaccine, and optimal supportive care and therapeutic strategies for all at risk groups as a key research priority. Research investments should be prioritised into vaccines and treatment strategies that will be accessible to high-risk populations in affected regions during the outbreak, to protect populations, improve individual outcomes and facilitate outbreak control.